2019
DOI: 10.1007/s11940-019-0544-7
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Abnormalities in Multiple Sclerosis

Abstract: Purpose of review: This review summarizes the most well documented sleep disorders seen in patients with Multiple Sclerosis (MS), with a special focus on the impact on quality of life. Recent findings: Sleep abnormalities in patients with MS are a multifactorial and relatively complex issue affecting approximately 60% of the patients while the pathophysiology of these symptoms is not fully understood. Circadian rhythm disorders and increased levels of Pro-inflammatory Cytokines have been recognized as potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 71 publications
1
34
1
5
Order By: Relevance
“…Although sleep may affect myelin, there is also evidence showing that primary deficits in myelin can lead to sleep and circadian disorders. For example, multiple sclerosis (MS), an autoimmune and degenerative disease characterized by CNS demyelination is frequently associated with sleep disorders, including insomnia, restless legs syndrome, periodic limb movement disorders, REM sleep behavior disorder, and sleep‐related breathing disorders (Veauthier, ; Foschi et al, ; Sakkas et al, ). Physical and psychological factors such as pain, anxiety and mood disorders, and nocturnal discomfort may all contribute to sleep disturbances in MS.…”
Section: Sleep and Myelinmentioning
confidence: 99%
“…Although sleep may affect myelin, there is also evidence showing that primary deficits in myelin can lead to sleep and circadian disorders. For example, multiple sclerosis (MS), an autoimmune and degenerative disease characterized by CNS demyelination is frequently associated with sleep disorders, including insomnia, restless legs syndrome, periodic limb movement disorders, REM sleep behavior disorder, and sleep‐related breathing disorders (Veauthier, ; Foschi et al, ; Sakkas et al, ). Physical and psychological factors such as pain, anxiety and mood disorders, and nocturnal discomfort may all contribute to sleep disturbances in MS.…”
Section: Sleep and Myelinmentioning
confidence: 99%
“…Multiple sclerosis (MS) is a chronic autoimmune, inflammatory, and neurodegenerative disease characterized by axon demyelination in different parts of the brain and/or spinal cord which may cause physical and cognitive symptoms, sensory impairments, and depressed mood. 1 Sleep disorders of multifactorial nature and unknown pathophysiology affect approximately 60% of patients with MS. 2 Several types of sleep disorders are prominent in patients diagnosed with MS such as insomnia, restless leg syndrome (RLS), periodic limb movement disorder (PLMD), obstructive sleep apnea due to respiratory problems, and daily excessive sleeping or narcolepsy. 3 Sleep disturbance in MS, specifically insomnia, causes excessive limitations in patients' physical and cognitive skills and contributes to increased feelings of fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective study of sleep quality in MS, Kotterba et al (110) found that patients with poor sleep had significantly poorer physical health, greater fatigue, and more severe depression and anxiety. Sleep abnormalities in patients with MS are a multifactorial issue, with circadian rhythm disorders and increased levels of proinflammatory cytokines apparently affecting sleep homeostasis (111). Therefore, sleep-improving practices are proposed to be integrated into the treatment procedures in MS (112).…”
Section: Discussionmentioning
confidence: 99%